Artificial Intelligence Assistance and Cognitive Abilities: Harnessing AI-Assisted Heuristic Methods for Transitioning from Critical to Creative Thinking in English Language Learning - Zahra Sadat Roozafzai (Educational Challenges)
Transitioning from critical to creative thinking is an essential component of English language learning, fostering problem-solving abilities, innovative idea generation, and effective communication skills.